2010
DOI: 10.1007/s00266-010-9483-0
|View full text |Cite
|
Sign up to set email alerts
|

Histological Features of Periprosthetic Mammary Capsules: Silicone vs. Polyurethane

Abstract: Synovial metaplasia was seen in the capsular tissue from both types of implant, but more so from capsules surrounding polyurethane implants more than 5 years old. The density and orientation of the collagen fibers and the foreign body reaction were very similar for the two types of implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
2
22
1
Order By: Relevance
“…Partially agreeing with Bassetto et al 17 , who obtained the presence of synovial metaplasia in the polyurethane and textured groups, which was bigger in the polyurethane group, in this study was found this variable, however, there was no difference between the groups. The same authors concluded that synovial metaplasia is the most important protective factor against capsular contracture.…”
Section: Evaluation Of Synovial Metaplasiasupporting
confidence: 50%
See 1 more Smart Citation
“…Partially agreeing with Bassetto et al 17 , who obtained the presence of synovial metaplasia in the polyurethane and textured groups, which was bigger in the polyurethane group, in this study was found this variable, however, there was no difference between the groups. The same authors concluded that synovial metaplasia is the most important protective factor against capsular contracture.…”
Section: Evaluation Of Synovial Metaplasiasupporting
confidence: 50%
“…In according to Bassetto et al 17 , the foreign body reaction was bigger in the polyurethane group. In the textured group, this reaction was present in all members in a milder way, differing from the present study in which the foreign body reaction was absent in the textured group, although this study has been carried out in rats and the other in humans.…”
Section: Evaluation Of Foreign Body Reactionmentioning
confidence: 99%
“…In contrast, PU was associated with a much greater inflammatory response, with a persisting insulation of the patches and, occasionally, granulomas, which have also been reported in other applications. 37,38 Whether a physicochemically different PU might more favorably affect host tissue responses will be the subject of future investigations.…”
Section: Figmentioning
confidence: 99%
“…Furthermore, this PSE is not consistently reported although there appears to be a higher prevalence with textured implants [20, 21]. While not used as frequently as textured or smooth implants, polyurethane foam-coated implants have been reported to generate a similar layer [22]. More recently, the inner layer has been identified as a metaplasia like synovial layer [3, 9, 24] consisting of macrophages and fibroblasts [23], and at this point, both names are used to describe the same layer [21].…”
Section: Introductionmentioning
confidence: 99%